Ex-post Impact Assessment of Fertilizer Microdosing as a Climate-Smart Technology in Sub-Saharan Africa - Murendo, C; Wollni, M (2015)
Microdosing refers to the application of small quantities of fertilizer with the seed at planting time or as top dressing three to four weeks after emergence. Microdosing provides sufficient nutrients especially on poor soils or degraded lands in amounts that are not too costly and are not damaging to the environment. Microdosing has been identified as a climate smart technology (The Montpellier Panel, 2013). Apart from being a climate smart technology, microdosing can be considered a pathway for the intensification of agricultural systems in Sub-Saharan Africa. Building on cross-sectional data from a recent survey on 415 smallholder farmers (193 microdosing adopters and 222 non-adopters) located in eight semi-arid districts of Zimbabwe, the results of this study demonstrate that microdosing increase crop production and productivity; reduce output and yield risk as well as improve food security.